APLIKASI SISTEM PAKAR DALAM MENDETEKSI KERUSAKAN AC RUMAH BERBASIS ANDROID DENGAN MENGIMPLEMENTASIKAN METODE CERTAINTY FACTOR - Yudo Bismo Utomo (Politeknik Bisnis Indonesia, 2021)
The current global warming season, Air Conditioning or AC, is a tool that is very useful for the community, because AC can cool a room. With its ability to cool a room, this air conditioner is often used continuously by the public, which makes it quickly damaged. When this AC device is damaged, people are confused and restless in repairing it. Moreover, coupled with the current Covid-19 pandemic, people are increasingly afraid to use the services of an AC technician, for fear of contracting the corona virus. This problem can be overcome by building a system where the system can help the community in diagnosing AC damage. The system is called an expert system to diagnose damage to home air conditioners using the Android-based certainty factor method. The result of this research is that with the application of this expert system, it can help the community in diagnosing AC damage and the level of accuracy in diagnosing AC damage using the certainty factor method is 80%.